African Catholic : decolonization and the transformation of the Church - Foster, Elizabeth Ann, 1976- (Harvard University Press, 2019)
This book examines French history, African history, the history of Catholicism, and religious studies. The book approaches the history of late colonialism and decolonization in French sub-Saharan Africa from a political and cultural perspective, by examining it through the prism of religion. Drawing on a plethora of African and French voices, it brings to life a Franco-African Catholic world that had been forged by conquest, colonization, missions, and conversions, and still exists today. Its denizens were preoccupied with the future of France's African colonies, the place of Catholicism in Africa, and whether their personal loyalties should lie with the Vatican, France, or emerging African states. Many leading African intellectuals were Catholics, and the book shows that there was an important Catholic strand of the negritude movement, which has been completely ignored by scholars and impacted the church at the highest levels. This finding contributes to the book's story of Catholic reform at mid-century, showing how decolonization was a pivotal factor in the reorientation of the church at Vatican II.--description provided by publisher.